Comparison of the Number of Gram Bacilli in Broncial Secretion and Heart Blood and Staying Time in the Morgue in Autopsy Cases of Hospitals and Non-Hospitals - Çakan, Hüseyin; Kocazeybek, Bekir; Öz, Vecdet (The Bulletin of Legal Medicine, 1996)
Specimens obtained from bronchial mucus and heart blood of 120 cadavres who were sent to the morgue of Forensic Medicine Institution for necropsy are cultured for gram negative bacteria repeatedly for 1-3 days. 60 of the 120 cadavers were belonging to the hospitalized individuals with different death causes. The remaining cadavers were belonging to the individuals died out of hospital due to different causes. We tried to determine the occurrence, density and the genus and species distribution of the isolated gram negative bacilli. We also tried to determine the correlation between the growth rates and the time for which the cadavers kept in the morgue. The cadavers were separated into two groups according their origins. Although there was no significant difference between two groups regarding the bacterial growth rates in both of the specimens (p greater than 0.05), the growth rates were slightly higher in the cadavers originated from the hospitals. This finding demonstrated the importance of the nosocomial microflora on the post-mortem bacterial contamination. The comparison of the growth rates in the relevance to the storage time in the morgue revealed that in contrast to the other group there was negative correlation between the storage time and bacterial growth rate in the hospitalized group (p less than 0.002). Our data showed that the hospitalized cases are exposed to a heavy bacterial contamination whereas other necropsy cases belonging to non-hospitalized group have normal microflora because of preserved mucosal barrier. In addition the isolation of Escherichia coli as the predominating organism made evident the role of colonic flora in the postmortem bacterial contamination. Keywords: Hospital Autopsies, Non-hospital Autopsies, Bronchial Mucus, Heart Blood, Gram Negative Rods.